Challenges of risk-based monitoring of clinical trials. (3rd July 2015) - Simović, Marko; Nikolić, Nataša
Abstract: The oversight of monitoring activities in clinical trials generally comes from the ICH GCP Guidelines and covers a wide range of responsibilities: trial progress oversight, adherence to the Study Protocol, Standard Operating Procedures, Good Clinical Practice, applicable regulatory requirement(s) and Source Data verification vs accuracy and completeness of the Case Report Form entries. Risk-based monitoring was developed and adopted by Sponsors, Investors, and CROs to decrease the costs of clinical trials and make study management more effective. Both the EMA and the FDA support such an approach with their papers. Interestingly, the review of the EMA "Annual report of the GCP Inspectors working group in 2012" has consistently shown persistence of a significant number of findings in fields/areas of monitoring that cannot be fully or partially captured with a centralized or targeted monitoring approach and cannot be identified, such as essential documents, presence and adherence to SOPs, trainings, and the quality of source documentation. Such results open up new challenges for Sponsors, CROs, and other stakeholders. As long as all current ICH GCP Guidelines are a cornerstone of clinical research, monitoring plans and risk assessments will include overseeing a significant pool of additional aspects, apart from the SDV.